Influence of 1D and 2D carbon nanostructures in silica-based aerogels. (15th August 2021) - Lamy-Mendes, Alyne; Malfait, Wim J.; Sadeghpour, Amin; Girão, Ana V.; Silva, Rui F.; Durães, Luísa
Abstract: Carbon nanostructures-silica aerogel composites were synthesized and characterized to assess the effect of carbon nanotubes (CNTs) or graphene oxide (GO) on the silica aerogel properties. The sol-gel chemistry was based on methyltrimethoxysilane (MTMS) and 3-aminopropyltrimethoxysilane (APTMS) as silica precursor system, with varying amounts of APTMS (0–20% mol of Si). APTMS significantly impacted the materials' physical properties. The chemistry and microstructure were investigated by FTIR, NMR, TEM, SEM, SAXS and BET. The addition of CNTs induced the growth of the silica matrix around them; thus, an elongated shape was observed in the silica structural units. APTMS and CNTs have a synergistic effect on the mechanical properties, increasing the Young's modulus up to 14 MPa. Small amounts of carbon materials (∼1 wt%) in the MTMS-matrix improved its thermal insulation property, particularly for temperatures above 50 °C. In terms of electrochemical properties, the carbon nanostructures lead to higher specific capacitances and a reduction in resistance. The characterizations here performed allowed a better understanding of the interactions between the silica and carbon phases. The possibility to obtain materials with tailored properties demonstrates their application potential in several areas, such as thermal insulation and energy storage. Graphical abstract: Image 1 Highlights: CNTs and GO were incorporated into MTMS-based silica aerogel networks. CNTs changes the silica network morphology to more elongated structural units. Small amounts of CNTs enhance the thermal insulation of the silica aerogels. APTMS and CNTs have a synergistic effect leading to higher Young's modulus. Addition of CNTs or GO improves the electrochemical performance of silica aerogels.